2020
DOI: 10.26710/jafee.v6i4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Financial Performance: A Meta-Analysis Study

Abstract: Based on the meta-analysis of 67 empirical research papers, this research extends prior reviews / meta-analysis studies by investigating the link of corporate governance (CG hereafter) mechanisms with firm financial performance. Further, this research contributes to the extant literature by making comparison of usefulness of CG mechanisms in both developed and developing countries. CG mechanisms appear to play differential role in driving corporate financial performance in both developed and developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 111 publications
1
9
0
Order By: Relevance
“…Many studies examine the insider ownership-performance relationship and find mixed results. Some studies find positive relation (Kaserer & Moldenhauer, 2008;Hu & Zhou, 2008;Katper et al, 2018), few studies observe negative (Fahlenbrach & Stulz, 2008;Shah et al, 2011;Ali et al, 2020;Vintilă & Gherghina, 2015). Yet some others find no relationship (Demsetz & Lehn, 1985;Abdullah et al, 2011;Hamza & Suman, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies examine the insider ownership-performance relationship and find mixed results. Some studies find positive relation (Kaserer & Moldenhauer, 2008;Hu & Zhou, 2008;Katper et al, 2018), few studies observe negative (Fahlenbrach & Stulz, 2008;Shah et al, 2011;Ali et al, 2020;Vintilă & Gherghina, 2015). Yet some others find no relationship (Demsetz & Lehn, 1985;Abdullah et al, 2011;Hamza & Suman, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…Further, a large increase in managerial ownership is not related to firms' value. Ali et al (2020), based on the meta-analysis of 67 studies across developed and developing countries, conclude that inside shareholding strongly negatively affects firms' performance in developing countries. However, inside ownership seems not influential in affecting firms' performance in developed countries.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The results are conflicting in case of developing countries where financial performance of firms appears to be negatively associated with board independence. This difference can be attributed to different institutional settings in both developed and developing countries (Ali et al, 2020). In China, the ownership concentration and degree of board independence are closely related to a firm's performance-but only in the case of larger companies.…”
Section: Corporate Governance (Cg) and Corporate Performance (Cp)mentioning
confidence: 99%
“…They found that board structure and size had a significant impact on the firm's performance through monitoring. In their meta-analytic study, Ali et al (2020) have pointed out contrasting effects of board independence, board meetings and board structure on firm performance in CG studies carried out in the Indian context. Nevertheless, this is an indicator about the prominence of the structure and function of the board as well as the independence of directors and their role in contributing to firm performance.…”
Section: Narayana Murthy Committee (2003)mentioning
confidence: 99%